USE OF PECTOLVAN C IN THE TREATMENT OF PNEUMONIA IN CHILDREN - Ibragimova, Марина (International Journal of Scientific Pediatrics, 2025)
Introduction. Pneumonia in children remains one of the most pressing problems in pediatrics, as it is one of the leading causes of child mortality, especially in young children. Every year, millions of cases of pneumonia in children are registered worldwide, especially in countries with a low level of medical care, and can lead to serious complications (pleurisy, respiratory failure). Pneumonia can be caused by various microorganisms (viruses, bacteria, fungi), which complicates diagnosis and treatment. In addition, bacterial resistance to antibiotics is growing, making therapy less effective. Diagnostic problems – in young children, pneumonia symptoms may be vague, making timely diagnosis difficult and increasing the risk of delayed treatment. Pneumonia in children is one of the most common causes of hospitalization, characterized by signs of respiratory distress caused by difficulty in expectorating thick sputum. The aim of the study was to evaluate the effectiveness of using Pectolvan C in the treatment of pneumonia in children. Materials and methods: 54 patients aged 4-12 years, hospitalized in the pediatric departments of the Samarkand branch of the Russian Scientific Center for Emergency Medical Care, were divided into two groups depending on the therapy. The main group (27 children) received complex treatment with the addition of Pectolvan C in an age-appropriate dosage. The control group (27 patients) received only standard complex therapy. Results and conclusions: The effectiveness of Pectolvan C was assessed by comparing the dynamics of the condition of patients in both groups for 10 days. The results showed that Pectolvan C is an effective combination drug with mucolytic and expectorant properties for the treatment of pneumonia. Ease of use, the presence of a liquid form, as well as the absence of side effects allow us to recommend this drug for widespread use in pediatric practice in the treatment of inflammatory diseases of the respiratory tract.